Analisis Kebutuhan Bimbingan Pribadi Sosial Berbasis Context, Experience, and Reality (CER) untuk Meningkatkan Karakter Kebajikan Siswa Sekolah Menengah Pertama - Hambali, IM (Jurnal Kajian Bimbingan dan Konseling, 2019)
The general objective of the study is to describe the needs of junior high school counselor toward CER-based socio-personal guidance service in order to improve the virtue of junior high school students. During the conduct of the study, the researcher implemented the survey design in order to attain the description data. The results of the study show that the counselors need CER-based media for improving the virtue of the junior high school students. Therefore, the counselor should search, find, create and even design the CER-based service media.